STUDENTS’ ERRORS IN WRITING NARRATIVE TEXT AT SMP NEGERI 3 SIDIKALANG - Stefani Harupaty Mahardika; Indra Hartoyo (Universitas Negeri Medan, 2022)
The purpose of this study to determine the types of errors found in the narrative text written by students of SMP Negeri 3 Sidikalang. Errors are analyzed to find the dominant type., and the reason they made the mistake This study used descriptive qualitative method. The object of this research is the 8th grade students at SMP Negeri 3 Sidikkalang. From the findings in the field, the writer finds that there are types of errors that come from the grammatical aspect. namely: sentence patterns, word order,concord, tenses. then the researcher studied and concluded. that the highest error is in the writing error of tenses. with a yield of 68.13%. and the lowest in the sentence pattern as much as 1%. And the reasons students make error because they do not understand the structure of English writing and some students think that writing in English is the same as writing in Indonesian. Errors are like Overgeneralization: Ignorance of rule restrictions Incomplete application of rules Incorrect concept HypothesizedKey Words: Error Analysis,grammatical error', Narrative Text